Stigmatized places as therapeutic landscapes: The beneficial dimensions of river-bottom homeless encampments (Medicine Anthropology Theory, 2020)
Urban rivers in the United States have frequently been sites of long-term homeless encampments. Recent efforts to ‘restore’ these marginal waterways have focused on removing such camps, an approach that is justified in terms of concern for the health of both waterways and people. This article explores the intersection of landscape health and human health, based on twelve months of ethnographic research on the ecological restoration of the Ventura River in southern California. I argue that river-bottom camps contribute to the health and well-being of residents by helping them resist social exclusion and mitigate experiences of violence and stigma. It is important to recognize this complexity so that logics of exclusion are not unintentionally reproduced in how landscapes are understood, which can legitimate actions, such as camp removals, that cause marginalized communities additional harm. Embracing the complexity of therapeutic landscapes opens up possibilities for more just ways of restoring the health of human and nonhuman natures.